THE NFLUENCE OF THE GEOMETRIC SHAPE ABOVE THE VULNERABILITY OF BUILDINGS - KULA TYPE FROM OLTENIA AND MUNTENIA REGIONS - Anca Mihaela BARBU; Madalina Xenia CALBUREANU; Diana Mara CALBUREANU; Gelica STANESCU; Ramona Maria PINTOI (Journal of Industrial Design and Engineering Graphics, 2019)
The main goal of this paper is to highlight the vulnerability during the life time of kula buildings from Oltenia and Muntenia Regions from Romania. This research highlights the characteristic features of massive kula type buildings by masonry built before 1900. A general presentation of these buildings is being performed, from the point of view of unique and particular features, in two distinct cases. The analysis carried out highlights common and different features for each construction. The behavior and the previsions about the lifetime duration of the massive masonry are influenced by parameters such as the constructive system, the geometric shape, the buildings materials properties. These are the parameters analyzed in this paper in order to be used as input in modeling the structures subjected to occasional loads (strong winds, massive snow accumulations, earthquakes, extreme temperatures, humidity, erosion and biological degradation). In such situations the destruction of the masonry elements and the collapse occur due to the accumulated fatigue in the component elements. All the conclusions can be used for performing a fatigue analysis of these buildings for determining the expected life duration.